HEMORRHAGIC DISEASE OF NEWBORNS WITH LATE DEBUT - A. I. Lobanov; O. G. Lobanova ("Paediatrician" Publishers LLC, 2011)
The article describes the problems of hemorrhagic disease of newborns with late debut. Prophylaxis of hemorrhagic disease in maternity hospital is performed for not all newborns. The clinical analysis of 9 cases of disease is performed. Dangerous feature of late debut of hemorrhagic disease (after 1st month of living) is the development of massive intracranial hemorrhage on the basis of hemorrhagic diathesis. Late debut of hemorrhage as a result of vitamin K deficiency is characterized with three factors: absence of hemorrhagic disease prophylaxis, breast feeding of a child and transitory cholestasis.